Corporate venture capital and the nature of innovation - Hannes Maxin (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper investigates a model where two corporate venture capital firms (CVCs) decide whether to finance a new venture stand-alone or together, called syndication. The CVCs obtain a cash flow if the venture succeeds. In addition, the venture has a positive or negative effect on an asset of the CVCs parental companies. This effect may differ among the parental companies. I show that the CVC faced with the weaker positive effect becomes the stand-alone investor only if the expected cash flow is low. Otherwise, in equilibrium, there are only syndicates or stand-alone investments of the CVC with the stronger positive effect. However, if one CVC faces a positive effect on its parental company's asset whereby the opponent faces a negative effect, then a syndicate is still possible. The model generates empirical predictions for syndicates consisting of several CVCs.
Keywords: G24; M13; 330; Corporate Venture Capital; Venture Capital; Nonmonetary Support; Nature of Innovation